Global teacher. global learner - Pike, Graham; Selby, David (London : sydney ; Hodder nd Stoughton, 1990)
This handbook for teachers explores and develops the theory and practice of global education, as well as offering an extensive range of practical activities for the primary and secondary classroom. Important ideas and issues are presented, along with suggestions for further reading.
Includes bibliography and index.
Keywords: International education -- Great Britain; Education internationale -- Méthodes actives; International education